Penerapan Metode Tutor Sebaya untuk Meningkatkan Hasil Belajar Mata Pelajaran Matematika Materi FPB dan KPK pada Siswa Kelas IV SDN 1 Langkapura - Mardiana Mardiana (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
This type of research is classroom action research. The subjects of this study were 40 grade students of SDN 1 Langkapura for the 2018/2019 academic year, with a total of 40 students consisting of 21 male students and 19 female students. Data collection techniques used test and non-test techniques. The results showed that students' completeness in classical learning increased from 57.5% in the pre-cycle to 70% in the first cycle and increased again to 85% in the second cycle. The data has reached the set success indicator, which is 85%. The average score of the students' formative tests increased from 58.0 in the pre-cycle stage to 69.75 in the first cycle and to 76.50 in the second cycle. These data have reached an indicator of research success, namely the average score of students ≥ 60. The number of students who scored above the KKM has also increased. In the pre-cycle stage there were 23 students or 57.5%, increasing in the first cycle to 28 students or 70% and again experiencing an increase in the second cycle to 34 students or 85%. This data has reached an indicator of research success, namely the number of students who score above the KKM by 75%.